(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article covers the issues of developing students’ geometric competencies in the process of teaching geometry in grades 10-11 of general education schools in the context of New Uzbekistan. Innovative methods and technologies for distance learning based on information and communication technologies have been developed to improve this process. The pedagogical advantages, technical capabilities, and effectiveness of using distance learning have been practically studied and proposed.